ANALISIS PENGARUH KUALITAS INFRASTRUKTUR JALAN TERHADAP HARGA-HARGA HASIL PERTANIAN DI KECAMATAN DOLOK SILAU - Sry Devi Tarigan; Rahmat Syumanjaya (Ekonomi dan Keuangan, 2013)
The purpose of this research was to determine the effect the road infrastructure quality to the system of agriculture products marketing in Dolok Silau and to determine the effect of the road infrastructure quality to the transportation costs of the agriculture products marketingas well as to determine the effect of the road infrastructure quality to the prices of agriculture products in Dolok Silou. The method of analysis used in this research is path analysis. The dependent variable in this research is the cost of transportation, marketing and pricing system of agriculture products, while the independent variable is the quality of the roadinfrastructure. The results obtained are as follows: the effect of the road infrastructure quality to the cost of transportation is negative; the effect of the road infrastructure quality to the marketing system is negative; and the effect of the road infrastructure quality to the price of agriculture products is positive.Keywords: quality of road infrastructure, transportation cost, marketing system and price of agriculture of products